2008
DOI: 10.1111/j.1464-410x.2008.07465.x
|View full text |Cite
|
Sign up to set email alerts
|

A model of catheter‐associated urinary tract infection initiated by bacterial contamination of the catheter tip

Abstract: extracted from selected patient catheter isolates and the DNA fragment of 16S ribosomal RNA was amplified by polymerase chain reaction and confirmed by DNA sequencing. The DNA sequences from the isolates obtained from different catheter sections and from urine in the same patient were compared. RESULTSAfter 1 day of catheterization there was significant bacterial growth on the outside of all the segments of patient catheters; there was significant growth on the inside of all segments by 4 days. Higher viable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
29
3
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 25 publications
(38 reference statements)
8
29
3
2
Order By: Relevance
“…At the species level, the most abundant phylotypes were representative of microorganisms that colonize and/or infect humans, including Pseudomonas aeruginosa, Klebsiella pneumoniae, Staphylococcus epidermidis, Streptococcus pneumoniae , Escherichia coli, Enterococcus faecalis, and Propionibacterium acnes. A recent, culture-dependent analysis of catheter biofilms also reported the identification of similar microorganisms, including Staphylococcus epidermidis, Enterococcus faecalis, Pseudomonas spp, and Klebsiella spp [15]. Many taxa were identified in multiple catheters (prevalences ranged from 13%–63%).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…At the species level, the most abundant phylotypes were representative of microorganisms that colonize and/or infect humans, including Pseudomonas aeruginosa, Klebsiella pneumoniae, Staphylococcus epidermidis, Streptococcus pneumoniae , Escherichia coli, Enterococcus faecalis, and Propionibacterium acnes. A recent, culture-dependent analysis of catheter biofilms also reported the identification of similar microorganisms, including Staphylococcus epidermidis, Enterococcus faecalis, Pseudomonas spp, and Klebsiella spp [15]. Many taxa were identified in multiple catheters (prevalences ranged from 13%–63%).…”
Section: Resultsmentioning
confidence: 92%
“…Diverse microbial species have been identified from catheter biofilms by microbiological culture [5], [13], [14], [15]. However, Nickel et al [10] reported that although multiple morphological types were observed to colonize Foley urinary catheters, only a small fraction of the attendant microorganisms could be detected by traditional microbiological culture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the introduction of closed drainage systems, the incidence of catheter-associated UTI via ascending routes has been reduced. Barford et al reported in an experimental model that most bacteria gain access to the bladder along the outside of the catheter [16]. However, their study included data from a short period of up to 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…1 Las IVU pueden complicarse con bacteriemia y sepsis, lo cual incrementa la morbimortalidad, los días de estancia hospitalaria y los costos relacionados. 2 En la última década se identificó un incremento en las cepas bacterianas resistentes en orina, tanto de pacientes de la comunidad como de pacientes hospitalizados. 3 Los pacientes con cáncer tienen mayor riesgo de infecciones debido a la inmunosupresión condicionada por la enfermedad per se, así como por el tratamiento, además de que algunos pacientes pueden presentar obstrucción anatómica del tracto urinario secundaria al tumor.…”
unclassified